Neoadjuvant Botensilimab/Balstilimab for localized mismatch repair proficient and deficient colon cancer: Results of the NEST phase 2 clinical trial - Manish A. Shah; Erika Hissong; Mehraneh D. Jafari; Pashtoon Murtaza. Kasi; Maider Astorkia; Sahrish Khan; Casey Owens; Zhengming Chen; Heather Yeo; Fabio Socciarelli; Sandipto Sarkar; Alana Nguyen; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: Effective immunotherapy for mismatch repair proficient colorectal cancer (CRC) is lacking. We examined the safety and efficacy of the novel next-generation immune activator/Fc-enhanced CTLA-4 inhibitor botensilimab (BOT) plus PD-1 inhibitor balstilimab (BAL) in the neoadjuvant setting for patients with resectable CRC. Patients and Methods: Patients 18 years of age or older with non-metastatic CRC awaiting surgical resection were eligible. BOT/BAL was administered followed by surgical resection. In cohort A, patients received BOT 75 mg d1 and BAL 240 mg d1, 15; in cohorts B/C, patients received 2 additional BAL doses (d29, 43). The primary study objectives were safety, feasibility (based on surgery delay), and pathologic response. Exploratory analyses examined changes in the tumor microenvironment. Results: Twenty-four eligible patients (26 tumors, n=22 pMMR; n=4 dMMR) were enrolled (two patients had synchronous primary tumors). Neoadjuvant BOT/BAL was safe and did not delay planned surgery in any patient. The major pathologic response rate was 41% (95% CI, 21%–64%) for pMMR, and 100% (95% CI, 40%–100%) for dMMR CRC. BOT/BAL was associated with significant anti-tumor effects in the tumor microenvironment, with an increase in the density and proportion of CD8+ T cells, a reduction in tumor infiltrating FOXP3+ Tregs, and evidence of increased immune cell-cell interaction in responding patients. Conclusions: These findings demonstrate safety, feasibility, and encouraging pathological responses for BOT/BAL in both non-metastatic pMMR and dMMR CRC. Tumor microenvironment remodeling suggests a robust anti-tumor immune response induced by immunotherapy. These data support the continued development of BOT/BAL in CRC.